Local steroid activation is a critical mediator of the anti-inflammatory actions of therapeutic glucocorticoids. Issue 2 (8th November 2020) - Fenton, Chloe; Martin, Claire; Jones, Rachel; Croft, Adam; Campos, Joana; Naylor, Amy J; Taylor, Angela E; Chimen, Myriam; Cooper, Mark; Lavery, Gareth G; Raza, Karim; Hardy, Rowan S
Abstract : Objectives: The enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) plays a well-characterised role in the metabolism and activation of endogenous glucocorticoids (GCs). However, despite its potent upregulation at sites of inflammation, its role in peripheral metabolism and action of therapeutic GCs remains poorly understood. We investigated the contribution of 11β-HSD1 to the anti-inflammatory properties of the active GC corticosterone, administered at therapeutic doses in murine models of polyarthritis. Methods: Using the tumour necrosis factor-tg and K/BxN serum-induced models of polyarthritis, we examined the anti-inflammatory properties of oral administration of corticosterone in animals with global, myeloid and mesenchymal targeted transgenic deletion of 11β-HSD1. Disease activity and joint inflammation were scored daily. Joint destruction and measures of local and systemic inflammation were determined by histology, micro-CT, quantitative RT-PCR, fluorescence activated cell sorting and ELISA. Results: Global deletion of 11β-HSD1 resulted in a profound GC resistance in animals receiving corticosterone, characterised by persistent synovitis, joint destruction and inflammatory leucocyte infiltration. This was partially reproduced with myeloid, but not mesenchymal 11β-HSD1 deletion, where paracrine GC signalling between cell populations was shown to overcome targeted deletion of 11β-HSD1. Conclusions: We identify an entirely novel component of therapeutic GC action, whereby following their systemic metabolism, they require peripheral reactivation and amplification by 11β-HSD1 at sites of inflammation to deliver their anti-inflammatory therapeutic effects. This study provides a novel mechanistic understanding of the anti-inflammatory properties of therapeutic GCs and their targeting to sites of inflammation in polyarthritis.